An alternative view to the tax evasion: the effect of tax morale on paying taxes in Macedonia and EU countries - Ristovska, Maja; Blazevski, Nikica Mojsoska; Nikolov, Miso (Serbian Journal of Management, 2013)
The tax noncompliance reduces government’s revenues and hence negatively affects citizens’ life through an inadequate provision of public services. In order to tackle tax evasion, governments usually rely on enforcement matters applying higher penalties and/or increasing the frequency of audits. On the other hand, in the last couple of years there is a growing literature and evidence suggesting that enforcement efforts alone cannot achieve significant increase on tax compliance. This literature links the willingness of citizens to pay taxes with the social values and norms, i.e. to the tax morale (Torgler 2005; Frey and Torgler 2007; Alm and Torgler 2006; Alm et al., 2011). If correct, the optimal government policies to tackle the tax evasion might defer considerably from the common ones. The aim of this study is therefore to investigate factors that shape the tax morale of Macedonian citizens, and to provide a comparative assessment with the EU countries. Our empirical investigation is based on the work of Torgler, through estimating an ordered probit model in which the dependent variable is the tax morale, and is regressed on a number of independent variables, age, gender, marital status, education, national pride, trust in institutions, happiness, life satisfaction, etc. Data for our study are from the fourth wave (2008) of the European Values Survey. Our main finding is that contrary to other studies for the European countries, the non-demographic factors are more important factors influencing tax morale in Macedonia than the demographic ones. The main contribution of this study is that it is the first attempt in our knowledge to investigate the factors driving the tax morale in Macedonia.